If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14c + -11 = 3(2c + 7) Reorder the terms: -11 + 14c = 3(2c + 7) Reorder the terms: -11 + 14c = 3(7 + 2c) -11 + 14c = (7 * 3 + 2c * 3) -11 + 14c = (21 + 6c) Solving -11 + 14c = 21 + 6c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-6c' to each side of the equation. -11 + 14c + -6c = 21 + 6c + -6c Combine like terms: 14c + -6c = 8c -11 + 8c = 21 + 6c + -6c Combine like terms: 6c + -6c = 0 -11 + 8c = 21 + 0 -11 + 8c = 21 Add '11' to each side of the equation. -11 + 11 + 8c = 21 + 11 Combine like terms: -11 + 11 = 0 0 + 8c = 21 + 11 8c = 21 + 11 Combine like terms: 21 + 11 = 32 8c = 32 Divide each side by '8'. c = 4 Simplifying c = 4
| 7=3-2+4x | | 6(w-2)+3w=24 | | (A+b)+3= | | 25xsquared-16=0 | | 3a+45+2a-10=180 | | .75n-2=-.875n+32 | | 3X-16=2N+18 | | 11x+10x=12x | | 5sinx+4cosx=0 | | 8c-(c-1)=9 | | -5x^2+39x+8=0 | | -24=3v+4(v+8) | | 4y+y+1=7y | | 3x-8+x+26=180 | | 6x-5(x-7)=-10 | | -24=3v+4(4+8) | | -5(r+7)=-87 | | 50+3x=x+82 | | -2=7(x-6)-2x | | 3x-7=5x-45 | | 9+8(5x+3)=-3-5(8x+3) | | -8x+9=-8x+5 | | -3.5x^2+42t+13=0 | | -3(2x-3)=4(x-7) | | 4(6x+2)=8(3x+1) | | .03x+.12(20)=.06+20+x | | 0.03=0.01+2.9 | | x^2-14x=-46 | | 46+12x=17x | | 1.2+12.2= | | 6x^2-38=0 | | -12+a=4 |